The impact of cognitive delay on pediatric heart transplant outcomes. (13th February 2017) - Prendergast, Christopher; McKane, Meghann; Dodd, Debra A.; Godown, Justin
Abstract: The presence of CD may be viewed as a relative contraindication to transplantation; however, its impact on pediatric HTx outcomes is poorly characterized. The aim of this study was to assess the impact of CD on pediatric HTx outcomes using academic progress as a surrogate measure of cognitive performance. The OPTN database was queried for all pediatric HTx recipients (2004‐2014) with reported academic progress. Multivariable analysis assessed the impact of DGL and the need for SE on post‐HTx graft survival. A total of 2245 children were included: 1707 (76%) within grade level, 269 (12%) with DGL, and 269 (12%) who required SE. The need for SE was not a risk factor for post‐HTx mortality; however, DGL was an independent risk factor for worse post‐HTx outcomes (AHR 1.4, 95% CI 1.02, 1.79, P =.03). Patients who require SE have similar outcomes compared to those without CD, likely secondary to significant parental involvement. Children with DGL demonstrate inferior post‐HTx survival, which could result from less parental oversight in children perceived to maintain compliance. Ensuring adequate social support for patients with evidence of CD may help to improve outcomes.